FACTORS EFFECTING OF HOTEL’S REVISIT INTENTION AMONG TOURISTS IN THAILAND: Received: 22 November 2024, Revised: 3 January 2025, January 2025, Accepted: 06 February 2025, Date of Publication: 16 July 2025 - Anusit Boontos,; Vichit Uon, (PEOPLE: International Journal of Social Sciences, 2025)
The objective of this article is to present knowledge derived from a literature review on causal factors of hotel’s revisit intention among tourists. The article to explain the meaning, background, components, and relationships of variable related to hotel’s revisit intention among tourists. Methodology by documentary research from 250 articles, with the source of the articles from various databases and analyzed data by content analysis. Based on the literature review found that the variables commonly used to study hotel’s revisit intention among tourists include customer experience, service quality, brand image, and customer satisfaction.